The Presentation of Self in Everyday Life: A Literature Review from Erving Goffman's Perspective (Oratio Directa, 2018)
This literature review examines Erving Goffman’s concept of self-presentation to understand how individuals manage impressions in everyday interaction. Dramaturgy frames social life as a performance involving actors, audiences, front regions, back regions, personal fronts, expressive equipment, and tims. Individuals adjust conduct according to setting and audience while seeking a favorable impression. The review also proposes an analytical framework for evaluating conduct across front, back, and private regions. Goffman’s perspective clarifies the relationship between social roles, impression management, and the contextual character of identity.
Keywords: Self-Presentation; Dramaturgy; Impression Management; Social Interaction; Erving Goffman